Pengaruh Kompetensi Terhadap Pengembangan Karir Dan Kinerja Guru Ekonomi SMA Negeri di Kota Jember - Wardhani, Roro Aditya novi; Wijaya, Shendy Andrie (Universitas Pendidikan Ganesha, 2020)
The purpose of this study is to analyze the role of career development in influencing competence on teacher performance. The study was conducted in all the high schools in Jember. The variables used in this study consisted of competence, career development and teacher performance. The type of research is a quantitative approach research with explanatory research methods. The population is all economics teachers in Jember City Public High School. The method used to determine the sample is purposive sampling with the criteria of permanent teachers who have worked for 2 years at a minimum. Data analysis method uses path analysis. After being analyzed, the results of the t test and path analysis, can be seen that competence has a significant effect on teacher career development and teacher performance. The analysis also shows that career development is able to mediate competence in teacher performance. A teacher who has competence, it will be easy to develop a career which will have an impact on performance. Professional teachers, will always have high demands in their work, so with competence and good career development, the performance will also be better.